2006
DOI: 10.1088/0954-3899/32/11/002
|View full text |Cite
|
Sign up to set email alerts
|

Transverse dynamics of Pb–Pb collisions at 40AGeV/cviewed by strange hadrons

Abstract: Abstract. The transverse mass spectra of K 0 S , Λ, Ξ and Ω particles produced in PbPb collisions at 40 A GeV/c have been studied for a sample of events corresponding to the most central 53% of the inelastic Pb-Pb cross-section. We analyze the distributions in the framework of a parameterized model inspired by hydrodynamics. The dependence of the freeze-out parameters on particle species and event centrality is discussed and comparisons with results at higher energy are shown.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…The bulk of the kinematical distributions of the particles produced in nucleus-nucleus interactions are expected to be shaped by the superposition of two effects: the thermal motion of the particles in the fireball and a pressure-driven radial (for m T = p 2 T + m 2 ) or longitudinal (for y) collective flow, induced by the fireball expansion. Studies of the m T spectra for , , hyperons and K 0 S , measured in Pb-Pb collisions at 158 and 40 A GeV/c were presented in [13,14], respectively. A study of the rapidity distributions at 158 A GeV/c was presented in [9].…”
Section: Strange Particle Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of the kinematical distributions of the particles produced in nucleus-nucleus interactions are expected to be shaped by the superposition of two effects: the thermal motion of the particles in the fireball and a pressure-driven radial (for m T = p 2 T + m 2 ) or longitudinal (for y) collective flow, induced by the fireball expansion. Studies of the m T spectra for , , hyperons and K 0 S , measured in Pb-Pb collisions at 158 and 40 A GeV/c were presented in [13,14], respectively. A study of the rapidity distributions at 158 A GeV/c was presented in [9].…”
Section: Strange Particle Spectramentioning
confidence: 99%
“…The 1σ contour plot in the freeze-out parameter space is shown in figure 2 for the most central 53% of the inelastic Pb-Pb cross section at 40 and 158 A GeV/c. More detailed analyses of the spectra [13,14] suggested that multi-strange hyperons could possibly undergo an earlier freeze-out than singly strange particles.…”
Section: Strange Particle Spectramentioning
confidence: 99%
“…The STAR fixed-target data, represented by red stars, are plotted alongside the data from several other experiments and are consistent with the trend. AGS and CERN experiments data is from [22][23][24][25][26][27][28][29][30][31][32].The K 0 S points have been scaled by a factor of 10 to make the plot easier to read.…”
Section: Pos(cpod2017)073mentioning
confidence: 99%
“…Descriptions of the NA57 apparatus can be found in [6][7][8], and in [3] in particular for the 40 A GeV/c set-up.…”
Section: The Na57 Set-up and The Data Samplementioning
confidence: 99%
“…The shapes of the m T = √ p 2 T + m 2 distributions are expected to be determined by an interplay between two effects: the thermal motion of the particles in the fireball and a pressure-driven radial flow, induced by the fireball expansion. In [3], we have analysed the m T distributions of strange particles ( , − , − , their anti-hyperons and K 0 S ) based on the blast-wave model [4], a parameterized model inspired to hydrodynamics. Due to the large number of particle species considered in that analysis, a simultaneous fit to the strange particle spectra allowed to disentangle the effect of the thermal motion from that of the collective expansion.…”
Section: Introductionmentioning
confidence: 99%